Social Entrepreneurship and Sustainable Development: A Bibliometric Analysis - Megha Garg; Parveen Kumar (Colombo Business Journal, 2023)
Social entrepreneurship incorporates characteristics from several disciplines, but lacks a dominant framework and literature though it is a rapidly expanding area. Therefore, our paper aims to carry out bibliographic mapping of relevant publications with the help of Biblioshiny software (R studio) and VoSviewer based on the publications in the Scopus database. The primary outcomes indicated an upsurge in the interest of scholars particularly after 2015. The analysis displays that a significant number of publications originated from industrialised Western countries and suggests that the research field is quite new-fangled and requires authors to collaborate with each other. Moreover, numerous sustainability-related themes have been discovered through keyword co-occurrence analysis. The themes identified here are significant for practitioners and regulators who seek to take advantage of the synergy existing between our research areas. The directions for future research studies can be guided by quantitative research from underdeveloped nations or emerging economies.